A Computer-Aided Justice Management System: A prototype for Universities in Uganda - Conrad M., Mubaraka; Moses, Agaba; Ngige, J. Ng’ang’a (International Journal of Engineering Research & Science, 2019)
Justice Management in any organisation is recipe for proper management and organisational prosperity. As error is to human, disputes are inevitable but should be resolved amicably. With a focus on higher institutions of learning justice administration and management is handy in managing competition and so profit maximization especially in the current privatization of higher education. The study aimed at designing a prototype for universities which ultimately helps local citizens to interpret law. Six universities were purposively selected and a cross sectional and design science research methodology employed. The study found that if improved the proposed justice management system would significantly reduce the prevailing challenges of case backlog, losses and postponed hearing records, timely and responsiveness of summons among others. However, in future the small messaging system (SMS) enabled systems could also be considered together with translator into major local languages.